One-Pot Synthesis of N-Arylated Amines by Hydroaminomethylation of 2,5-Dihydrofuran with Aromatic Amines - Zheng, Zhiwen; Wang, Lailai (Synthesis, 2019)
A new efficient catalytic system for one-step synthesis of N-arylated amines, for example, an important intermediate, 4-ethyl-N-[(tetrahydrofuran-3-yl)methyl]aniline, is achieved by using different rhodium precursor and phosphorus ligands catalyzed hydroaminomethylation of aniline and its derivatives with heterocyclic and/or cyclic olefins. By screening the reaction parameters, the optimal reaction conditions are found as follows: methanol as a solvent, PPh3 as a ligand, [Rh(cod)2]BF4 as a catalyst precursor, a P/Rh ratio of 5:1, syngas pressure 4 MPa (H2/CO = 3:1), 100 °C, 20 hours, and no additives. The conversion of aniline reaches >99% and the yield of N-[(tetrahydrofuran-3-yl)methyl]aniline is up to 99% using this catalytic system. Moreover, the reaction of aniline and various cyclic olefins is investigated under the optimal conditions, and excellent conversion and good yields are obtained.
Keywords: heterocyclic olefins; cyclic olefins; hydroaminomethylation; amines; phosphine/Rh; 2,5-dihydrofuran